Educational Honesty: The Main Philosophical Value in School - Fitriah M.Suud; Sutrisno Sutrisno; Abd. Madjid (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2019)
AbstractThis study aims at exploring the educational honesty that a school in Aceh has created to discover the fundamental principles and definitions of honesty education that schools have built up to promote integrity in the schools. Data collected through a qualitative approach, interview, observation, and documentation study. The results of this research showed that educational honesty could work well because it focused on universal, academic, and professional principles that established philosophical values. The definition of truth designed from the foundation level of schools, schools in general and taught in detail in the classroom. The concept of educational honesty is stronger because it has included in the Vision, Mission, Objectives, and School Programs. This research expected to offer a new idea of honesty education in schools.AbstrakStudi ini bertujuan untuk mengeksplorasi kejujuran pendidikan yang telah diciptakan oleh sebuah sekolah di Aceh untuk menemukan prinsip-prinsip dasar dan definisi pendidikan kejujuran yang telah dibangun oleh sekolah untuk meningkatkan integritas di sekolah-sekolah tersebut. Data dikumpulkan melalui pendekatan kualitatif, wawancara, observasi, dan studi dokumentasi. Hasil penelitian ini menunjukkan bahwa kejujuran pendidikan dapat bekerja dengan baik karena berfokus pada prinsip-prinsip universal, akademik, dan profesional yang menetapkan nilai-nilai filosofis. Definisi kebenaran dirancang dari tingkat dasar sekolah, sekolah pada umumnya dan diajarkan secara rinci di kelas. Konsep kejujuran pendidikan lebih kuat karena sudah termasuk dalam Visi, Misi, Tujuan, dan Program Sekolah. Penelitian ini diharapkan dapat menawarkan gagasan baru tentang pendidikan kejujuran di sekolah.How to Cite: Suud, F. M., Sutrisno, Majid, A. (2019). Educational Honesty: The Main Philosophical Value in School. TARBIYA: Journal of Education in Muslim Society, 6(2), 141-154. doi:10.15408/tjems.v6i2. 11769.